The Banana (Musa balbisiana Colla) Peels Flour Modulates HTR2B Receptor Expression in the Liver Diabetic Rats - Andreanyta Meliala; Paramita Narwidina; Herlin Ajeng Nurrahma; Irwan Supriyanto (HAYATI Journal of Biosciences, 2022)
Uncontrolled diabetes mellitus (DM) has been linked to depression and lipid metabolism impairment. Serotonin (5-HT) has been known to improve lipid metabolism and affect mood. The 5-Hydroxytryptophan (5-HTP) in banana peel flour (BPF) is a precursor to synthesize 5-HT in the body, which is linked to initiating liver regeneration via HTR2B receptors. The impact of 5-HTP in the diet on HTR2B receptor expression has yet to be thoroughly investigated. We aimed to elucidate the correlation between serum lipid profile and immobility time in Tail Suspension Test (TST) as depressive-like behavior and compare the expression of HTR2B receptor in healthy and diabetic rats. Male Wistar (Rattus norvegicus) rats were assigned to the control and treatment groups in a DM model with streptozotocin (60 mg/kg) injected intraperitoneally, then either fed standard diet or BPF 10% supplemented standard diet for 21 days. Immunohistochemical staining was used to examine the expression of 5-HT, HTR2B receptors. We determined that diabetic rats fed the standard diet supplemented 10% BPF group showed significantly lower concentrations of total cholesterol and triglycerides compared to diabetic rats fed a standard diet and it was positively correlated between total cholesterol and LDL with the duration of immobility time in TST. The average immunoreactivity score in diabetic rats fed 10% BPF was the highest among the other groups, indicating that the available BPF dose is sufficient for HTR2B activation, which will support the liver cell regeneration process, and should be investigated further.